Researching urban diversity and the (re-)production of whiteness: reflections on the purchase and challenges of sensory methods - Barwick-Gross, Christine; Chollet, Jari; Kulz, Christy (Frontiers in Sociology, 2025)
In this paper, we reflect on the purchase of sensory methodologies to research urban diversity and the (re-)production of whiteness. In the social sciences, scholars commonly rely on visual methods, using the ‘body as text’ (Stoller, 1997). Based on more recent advances in urban and migration studies, we seek to move beyond this Eurocentric focus, by asking how urban diversity is experienced through sounds and through smells. How individuals experience sensory inputs such as sounds and smells, and how they make sense of them, feeds into processes of boundary making and boundary crossing. The urban space is a prime context to study such processes, given that cities’ dense character and high diversity provide their residents with endless sensory stimuli. Based on sensory research in a highly diverse street in Berlin, we reflect on how smells and sounds contribute to creating hierarchies between (groups of) people, how they contribute to feelings of local belonging and home, or feelings of being out of place. We also reflect on the challenges of applying sensory methods. These refer to the relationship between participants’ embodied experiences and how they made sense of those discursively in group discussions; and about the implications of doing research on a highly mediatized street. With our focus on micro interactions, the (re-) production of space, and diversity, our findings add to the emerging field of ‘sensory urbanism’.